MODUL PERCOBAAN INTERFACING PORT PARALLEL DENGAN LIQUID CRYSTALL DISPLAY 2 LINE X 16 CHARACTER YANG DIDUKUNG BAHASA PEMROGRAMAN BORLAND DELPHI 7.0 - Sudi Suryadi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2013)
n principle computer can be used with various need, one of them can display aninformation to Liquid Crystall Display.In this research, displayed information amount to 2 line x 16 character which inputthrough computer by exploiting with paralell port, and also prosessed by computer program.Result of the process will be presented to Liquid Crystall Display panel, good for knowinginformation which input trough the keyboard.